The geopolitical changes in Europe and the Balkans and their impact on the Republic of (North) Macedonia since the beginning of the 21st century - Mariyana Stamova (Historijski pogledi)
The last decade of the 20th century is associated predominantly with the international consolidation of the Republic of Macedonia, whereas during the first decade of the 21st century the country faced grave international problems and confrontations between the Macedonian and the Albanian communities, as well as the dilemma of its further steps towards membership in the European and North Atlantic structures. On the verge of the new century, the state clashed with numerous domestic political problems and escalation of the inter-ethnic conflicts. The danger of the escalation and spreading of the ethnic conflict and its transformation into civil war was successfully averted with the help of the international community. From a foreign policy perspective, during the first decade of the 21st century the country had candidate status for EU membership and the doors of NATO were open for it. However, the main problem before its successful integration consisted in finding a solution to the issue of the country’s name in its dispute with Greece. In spite of the serious efforts of the Republic of Macedonia, the EU did not set a date for the start of the accession negotiations in the beginning of the second decade of the 21st century. On its part, NATO was ready for rapid accession of the Balkan state, but only after the dispute on its name had been resolved. That position was clearly outlined at the NATO Summit in Bucharest in 2008, when Albania and Croatia received invitations to join the Alliance, but Macedonia did not. The country thus remained with totally blocked dialogue with NATO and the EU on account of the demands of Greece concerning its name and the implementation of the good-neighbourhood policy. That in turn created a security threat and resulted in escalation of the inter-ethnic tension. The country’s growing destabilisation was strongly influenced by the deepening crisis in the domestic policy sphere in the autumn of 2012, provoked by the so-called “budget crisis.” It was connected with difficulties for adopting the new budget after it was blocked in the Assembly by the opposition. The political crisis continued in 2013, with the active help of the opposition, notably the left-wing Social Democratic Union of Macedonia that blocked on numerous occasions the Assembly’s work on various issues. On the domestic political level, presidential and extraordinary parliamentary elections followed, which created a new political tension. The political parties in the struggle for power very fiercely accused each other of incompetence and electoral falsification of the parliamentary elections. On the gender-political front, there was still the current issue of the blocking of the Republic of Macedonia's admission to the EU by Bulgaria and Greece. Macedonia accepted all the conditions set by Greece, including the change of the constitutional name to the Republic of North Macedonia in 2019. This motivated Bulgarian politicians to set some of their own conditions regarding language and history. Namely, it is known that Bulgaria does not recognize the existence of the Macedonian nation, its language and history, so it has created a new and further political problem. We should not forget the already existing problems.